Marlborough Recent Acquisitions. : Francis Bacon - George Grosz - Barbara Hepworth - Ernst-Ludwig Kirchner - RB Kitaj - Paul Klee - Henry Moore - Emil Nolde - Egon Schiele - Oskar Schlemmer - Karl Schmidt-Rottluff - Kurt Schwitters - Graham Sutherland. (London : Marlborough Fine Art Ltd., 1967)
Bacon, Francis ; Grosz, George ; Hepworth, Barbara ; Kirchner, Ernst Ludwig ; Kitaj, R.B. ; Klee, Paul ; Moore, Henry ; Nolde, Emil ; Schiele, Egon ; Schlemmer, Oskar ; Schmidt-Rottluff, Karl ; Schwitters, Kurt ; Sutherland, Graham
geboortedata per kunstenaar
Engels
Recent Acquisitions 1967, Marlborough Fine Art Ltd., London, July - August 1967
boek